Reference Genes for qPCR Analysis in Resin-Tapped Adult Slash Pine As a Tool to Address the Molecular Basis of Commercial Resinosis - de Lima, Júlio C.; de Costa, Fernanda; Füller, Thanise N.; Rodrigues-Corrêa, Kelly C. da Silva; Kerber, Magnus R.; Lima, Mariano S.; Fett, Janette P.; Fett-Neto, Arthur G. (Frontiers in Plant Science, 2016)
Pine oleoresin is a major source of terpenes, consisting of turpentine (mono- and sesquiterpenes) and rosin (diterpenes) fractions. Higher oleoresin yields are of economic interest, since oleoresin derivatives make up a valuable source of materials for chemical industries. Oleoresin can be extracted from living trees, often by the bark streak method, in which bark removal is done periodically, followed by application of stimulant paste containing sulfuric acid and other chemicals on the freshly wounded exposed surface. To better understand the molecular basis of chemically-stimulated and wound induced oleoresin production, we evaluated the stability of 11 putative reference genes for the purpose of normalization in studying Pinus elliottii gene expression during oleoresinosis. Samples for RNA extraction were collected from field-grown adult trees under tapping operations using stimulant pastes with different compositions and at various time points after paste application. Statistical methods established by geNorm, NormFinder and BestKeeper softwares were consistent in pointing as adequate reference genes HISTO3 and UBI. To confirm expression stability of the candidate reference genes, expression profiles of putative P. elliotti orthologues of resin biosynthesis-related genes encoding Pinus contorta β-pinene synthase (PcTPS-(−) β-pin1), P. contorta levopimaradiene/abietadiene synthase (PcLAS1), Pinus taeda -pinene synthase (PtTPS-(+) pin) and P. taeda -farnesene synthase (PtFS) were examined following stimulant paste application. Increased oleoresin yields observed in stimulated treatments using phytohormone-based pastes were consistent with higher expression of pinene synthases. Overall, the expression of all genes examined matched the expected profiles of oleoresin-related transcript changes reported for previously examined conifers.